2021
DOI: 10.1002/hyp.14113
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological trends and the evolution of catchment research in the Alptal valley, central Switzerland

Abstract: When the observation of small headwater catchments in the pre-Alpine Alptal valley (central Switzerland) started in the late 1960s, the researchers were mainly interested in questions related to floods and forest management. Investigations of geomorphological processes in the steep torrent channels followed in the 1980s, along with detailed observations of biogeochemical and ecohydrological processes in individual forest stands. More recently, research in the Alptal has addressed the impacts of climate change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Previous research reported a high similarity in the discharge regimes between the Alp river and its upstream torrents, one of which is the Erlenbach (Staehli et al, 2021). This finding has important implications As expected, using only five or fewer surveys in the CEASE method resulted in lower accuracy and sensitivity for both catchments (Figure 5).…”
Section: Evaluation Of the Cease Methodsmentioning
confidence: 65%
See 3 more Smart Citations
“…Previous research reported a high similarity in the discharge regimes between the Alp river and its upstream torrents, one of which is the Erlenbach (Staehli et al, 2021). This finding has important implications As expected, using only five or fewer surveys in the CEASE method resulted in lower accuracy and sensitivity for both catchments (Figure 5).…”
Section: Evaluation Of the Cease Methodsmentioning
confidence: 65%
“…This study was carried out in two sub‐catchments of the pre‐Alpine Erlenbach research catchment (Staehli et al, 2021; Figure 1): Langried (Lan) and Chaspersböden (Cha). The Erlenbach catchment (Erl) has an area of 0.7 km 2 and ranges in elevation from 1080 to 1520 m a.s.l.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A detailed description of the long-term hydrometeorological measurements in the Alptal catchment is provided by Stähli et al . 23 .…”
Section: Methodsmentioning
confidence: 99%